The Capability Upon Disaster Preparedness Amongst Malaysian Hospitals - Said, Noor Azzah (2022)
This study is hoped to contribute to the whole process and understanding of disasters that hospitals are called upon to manage. This area requires careful study within the context of institutional theory and organisational learning capability in assessing the factors contributing to hospital preparedness towards disasters as some areas require clarification and further work. This study specifically examined the institutional elements associated with hospital preparedness to manage disasters. The explanatory variables are modelled from the institutional theory where the elements are classified as coercive, mimetic, and normative pressure; and organisational learning capability where the elements are classified as clarity of purpose and mission, leadership commitment and empowerment, experimentation and rewards, transfer of knowledge, and teamwork and group problem-solving. This study used a quantitative approach with correlation research design to answer the research objectives, research questions, and hypotheses stipulated in the study. A total of 100 government hospitals in Malaysia were assessed to understand their level of disaster preparedness during the event of a disaster. SmartPLS was then applied to assess the relationship between the explanatory factors and hospital disaster preparedness. The findings reveal that Malaysian public hospitals are in category B, which requires intervention measures for hospitals to function during and after disasters. The findings also indicate that institutional pressure and organisational learning capability influence hospital disaster preparedness.